Gaston Bachelard et La poétique de la rêverie. Une interprétation écologique - Hess, Gérald (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
In this article, I support the thesis that the book La poétique de la rêverie can be interpreted from an ecological perspective. The proposed approach is not, however, that of scientific ecology, that is to say, an objective, third person approach; on the contrary, it is an extension of the approach adopted by Gaston Bachelard himself in his poetics, namely that of phenomenology. However, in order to suggest such a reading of the work, it is necessary to leave Bachelard’s psychological focus on poetic imagination and place his reflection in an ontological context. To do so, I rely on an acentric environmental aesthetic, then on a phenomenology of the flesh. The decentration of the self to which this double path invites us finally allows us to understand the daydreaming in an ecological sense, as statements about the world and not only as a psychology of the “dreamer”. Key Words: imagination, phenomenology, environmental aesthetics, Godlovitch, Merleau- Ponty